Organizational Culture under the Perspective of the Brazilian Regional Culture - Muzzio, Henrique (Review of Business Management, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->This essay has the objective of analyzing the Brazilian cultural context and its influence on the organizations universe from a cultural regional perspective that goes beyond the functionalist paradigm and advances through contemporary concepts, like cultural flows and the local cultural codes. In an international perspective, in studies that consider the perspective of cultural adaptation, it is possible finding a significant volume of research that emphasizes the distinctions between regions or nations. On the other hand, when it these studies deal with this perspective inside each culturally diversified country it seems that there isn’t the same expression in the rural areas. In Brazil there isn’t the same intensity of effort of research. Besides, in our country the cultural diversity is recognized, and the analyses that consider the influences of the culture variable can potentially contribute for the efficiency of the organization’s internal and external relations. It is defended that organizations need to contemplate in their actions what it is called local cultural legitimacy, especially when these organizations work in distinct contexts, respecting the local values and cultural practices. Brazil has different cultural regions where it is possible finding different consumers and employees and distinct cultural codes that indicate the need of different forms of management. Key words: <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Organizational culture. Regional culture. Brazil. Cultural legitimacy.